2017
DOI: 10.15666/aeer/1503_611620
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Three Potential Energy Crops: Common Mugwort, Cup Plant and Virginia Mallow on Western Lithuania’s Albeluvisol

Abstract: Abstract. Research on novel energy crops -common mugwort (Artemisia vulgaris L.), cup plant (Silphium perfoliatum L.) and Virginia mallow (Sida hermaphrodita Rusby) was set up on a naturally acid Albeluvisol in West Lithuania. The study was aimed to evaluate the effect of year (growing conditions), liming and nitrogen fertilization on biomass yield, its structure as well as lime and nitrogen use efficiency. In many cases, year (or growing conditions) and N fertilization were two determinant factors for all stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Although combine/forage harvesters are the most common harvesting equipment, alternatives are often used. Examples of machinery used to harvest S. hermaphrodita are: forage harvesters in combination with drum choppers or balers [19,66], self-propelled harvesters [67], mowers [22,30], or cutters [33].…”
Section: Harvesting Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although combine/forage harvesters are the most common harvesting equipment, alternatives are often used. Examples of machinery used to harvest S. hermaphrodita are: forage harvesters in combination with drum choppers or balers [19,66], self-propelled harvesters [67], mowers [22,30], or cutters [33].…”
Section: Harvesting Methodsmentioning
confidence: 99%
“…Some authors recommend splitting the application of nitrogen into two equal doses to maximize nitrogen use efficiency. The suggested timing is generally just before growth starts and then just before canopy closure in July [7,22,31,33] or more specifically at BBCH 11 [35]. Analysis of the macro-element composition of S. hermaphrodita showed a nitrogen content in the harvested stems of 7.9-12.8 g N DM kg −1 , which is the same order of magnitude as nitrogen found in the stems and branches of poplar SRC (Table 3).…”
Section: Nutrient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect seems to be due to an increase in shoot height, shoot diameter, and number of shoots per square meter (Borkowska et al ., ). Positive responses to NPK fertilization as well as to liming were observed from Sida grown on acidic soil in Lithuania (Siaudinis et al ., , ). Still, the biomass yields of Sida remained rather low in these studies even on the fertilized plots, and their average amounted to 6.6 t air‐dry mass across all treatments for three years of growth.…”
Section: Effects Of Fertilizationmentioning
confidence: 99%
“…At the same time, it is conducive to revitalizing and utilizing the original historical data, promoting the coconstruction and sharing of resources and environmental data, standardizing the release and exchange of forestry information, and laying the foundation for "digital forestry".Through theoretical analysis and experimental research, it is found that the dynamic monitoring method of forest coverage based on GIS proposed in this paper has the advantages of technical feasibility, management feasibility and basic feasibility. At present, the county (city), region (city, autonomous prefecture) and autonomous region governments at all levels have forestry authorities, the forestry authorities in autonomous region and parts of the region have established forest cover management or monitoring institutions, and the forestry stations network of towns (farms, pastures) below the county level is sound, which creates a management innovation for the dynamic monitoring system of forest cover(Siaudinis et al 2017). Conditions have been established, and the forestry departments at all levels can form a management system for dynamic monitoring of forest coverage by slightly adjusting their original internal institutions.…”
mentioning
confidence: 99%